The role of local government in Reog Ponorogo MSME empowerment: A regulator, facilitator, and catalyst - Ima Maulida; Amirul Mustofa; Eny Haryati (Universitas Muhammadiyah Malang, 2023)
This research aims to understand the role of the government as a regulator, facilitator, and catalyst in empowering MSMEs in Reog Ponorogo. The qualitative descriptive research method is used with data collection using observation, interviews, and documentation methods. The results of this research show that the role of local government as a regulator, facilitator, and catalyst in empowering MSMEs in Reog Ponorogo still needs to be improved. As a regulator, the local government should be able to create policies or regulations that agencies can implement to develop Ponorogo Reog MSMEs, such as agency uniform regulations that use Reog attributes in August. The government's role as a catalyst is to provide accessible trading permits for new MSMEs and provide stimulus in the form of people's business credit or KUR in collaboration with private parties in developing MSMEs with relatively simple application requirements.